The third trial of William Hone, on an ex-officio information. At Guildhall, London, December 20, 1817, before Lord Ellenborough and a special jury, for publishing a parody on the Athanasian Creed, entitled "The Sinecurist's Creed" (Hone, 1818)
In: The three trials of William Hone, [...]. PAMPHLET VOLUME.